Refractive index and temperature coefficient of refractive index of Al2O3- and SiO2-water nanofluids. (November 2022) - Yousefi, T.; Naylor, D.; Saghir, M.Z.
Highlights: Measurements are made of the refractive index and temperature coefficient of refractive index (∂n/∂T) for two nanofluids, Al2 O3 -water and SiO2 -water. For both nanofluids, the refractive index decreases with increasing temperature and increases with increasing particle concentration. The variation of refractive index is approximately linear with concentration. ∂n/∂T for Al2 O3 -water nanofluids can be approximated as that of water with an accuracy better than ±5% for a concentration φ < 1%. For SiO2-water nanofluid, ∂n/∂T can be approximated as that of water with an accuracy of better than ±5% for a concentration φ < 4%. Abstract: Measurements are made of the refractive index and temperature coefficient of refractive index (∂n/∂T) for two nanofluids, Al2 O3 -water and SiO2 -water, over the temperature range 20–40°C at a wavelength of 632.8 nm. These optical properties are needed for refractive index-based temperature and heat transfer measurements, particularly laser interferometry. A laser beam deflection technique is used to measure the refractive index of the nanofluids. The temperature coefficient of refractive index is determined by measuring the phase change with temperature, using Mach-Zehnder interferometry. Measurements are made for Al2 O3 -water nanofluids up to a weight-based concentration of ϕ = 20% and for SiO2 -water nanofluids up to a weight-based concentration of ϕ = 40%. The refractive index data are used to quantify the errors in interferometric temperature measurements produced by non-homogenous nanofluid suspensions. In the literature, the optical properties of dilute water-based nanofluids are sometimes assumed to be equal to those of water for interferometry experiments. The limits of this approximation are estimated. The current measurements indicate that ∂n/∂T for Al2 O3 -water nanofluids can be approximated as that of water with an accuracy better than ±5% for a concentration ϕ < 1%. For SiO2 -water nanofluid, ∂n/∂T can be approximated as that of water with an accuracy of better than ±5% for a concentration ϕ < 4%.